The dark maestro : [large type] a novel - Slocumb, Brendan (Random House Large Print Publishing, 2025)
"From the author of The Violin Conspiracy and Symphony of Secrets comes a mesmerizing page-turner about a young Black musical virtuoso at the peak of his career who's forced into hiding when his family runs afoul of a ruthless international cartel-and uses his music to fight back. Curtis Wilson is a classical music prodigy. Playing since the age of five, he is that rare performer who, through sheer force of will and phenomenal talent, has clawed his way out of inner-city DC and risen to the heights of the classical music world-soloing with the New York Philharmonic. Zippy, his father, is a midlevel drug dealer, and Larissa, his father's girlfriend, is a loving mother figure to Curtis and the heart of the family. Then, Zippy runs afoul of the kingpin who has provided his livelihood and nurtured his son's talents, and the family finds their lives in danger. With no choice but to run, they enter the witness protection program and abandon their former lives, including Curtis's extraordinary career. When law enforcement seems unable to bring the cartel down, Curtis, Zippy, and Larissa realize that their only chance of returning to the way things were is to take on the cartel themselves-their own way. A propulsive and moving story about sacrifice, loyalty, and the indomitable human spirit, Dark Maestro is Slocumb at the height of his powers"--